POTENSI PENERAPAN SMART TOURISM DI WISATA HALAL PANTAI LON MALANG KABUPATEN SAMPANG - Ahmad Farihin Eko Hadi; Rudi Hermawan; Adi Yono (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Tourism is a destination that is most popular with various groups, because tourism can make you feel more relaxed and at ease in between busy activities. Beaches are one of the most popular tourist attractions, currently the world is being hit by rapid developments to the point of development of technology, information and communication, so that with these conditions automatically the development of tourism destinations, especially beaches, must be related to conditions. at this time. The purpose of this material is to help halal Lon Malang beach tourism to increase tourism existence by implementing the smart tourism concept, and provide knowledge about the importance of the smart tourism concept in increasing tourist interest so that they can create a better travel experience, increase effectiveness, competitiveness, which will further lead to equitable sustainability. Also, readiness for halal tourism at Lon Malang beach in implementing the potential of Samrt tourism. This study uses descriptive qualitative data analysis techniques where the data used in this study were obtained from journals, scientific papers, and interviews with the leaders of halal tourism management of Lon Malang beach, Sampang Regency using a phenomenological approach. The results of this research are that if viewed in terms of the potential that exists in halal tourism, Lon Malang Beach is very ready to implement the smart tourism concept considering that there are facilities, services and human resources that support the implementation of the smart tourism concept, such as the implementation of an online ticket payment system, collaboration with well-known marketplaces in an effort to introduce tourism.